Rapid formation of 2-lithio-1-(triphenylmethyl)imidazole and substitution reactions in flow. Issue 11 (29th September 2021) - Wang, Simeng; Panayides, Jenny-Lee; Riley, Darren; Tighe, Christopher J.; Hellgardt, Klaus; Hii, King Kuok (Mimi); Miller, Philip W.
Abstract : The rapid formation and reaction of 2-lithio-1-(triphenylmethyl)imidazole in flow at ambient temperature is reported. Abstract : The functionalisation of imidazoles is a necessary step in the formation of many active pharmaceutical intermediates. Herein, we report a flow chemistry approach for the rapid and efficient formation of 2-lithio-1-(triphenylmethyl)imidazole at ambient temperature and its reaction with a range of electrophiles, achieving modest to high yields (40–94%) in short reaction times (<1 min). The method is amenable to the scale-up of this highly reactive lithio-imidazole intermediate.